Papa, PhD essays on fatherhood by men in the academy - Marotte, Mary Ruth.; Reynolds, Paige; Savarese, Ralph James; ebrary, Inc. (New Brunswick, N.J. : Rutgers University Press, 2011)
A collection of personal essays from men who wrestle with what it means to be a father in academia today. Organized in three sections, the stories of the contributors depict not merely a balancing act of parenting, teaching, and writing, but also the revelatory collision and occasional fusion of competing identities. Essays in the first section, "Fathers in Theory, Fathers in Praxis," focus on challenges related to merging work and parenting. The authors contemplate to what degree we engage our children in the academy, while also allowing them to grow independently, recognizing the challenge of keeping the roles of parent and teacher distinct. The second section, "Family Made," explores fatherhood against the grain and includes narratives of single dads, fathers raising children with disabilities, biracial families, and other "non-traditional" parenting situations. "Forging New Fatherhoods," the third section, articulates the strategies created by men to "balance diapers and a doctorate" or to reconcile fatherhood with professional ambition. The contributors' reflections reveal how fatherhood is instrumental to their successes and failures in the workplace, and demonstrate that the relationship between fatherhood and academia is a rich and legitimate subject for study.
Disney dad / Amitava Kumar -- Gaining a daughter: a father's transgendered tale / Lennard J. Davis -- Gifts from the sea / David G. Campbell -- The luck of the irish / F.D. Reeve -- Shifting the tectonic plates of academia / Jerald Walker -- Hair-raising experiences / John W. Wells -- A river runs through it: queer theory and fatherhood / Joseph Gelfer -- On writing and rearing / David Blake -- How to do things with words / Ira L. Strauber -- On fecundity, fidelity, and expectation: reflections on philosophy and fatherhood / J. Aaron Simmons -- Sheathing the sword / Gregory Orfalea -- Weighed but found wanting: ten years of being measured and divided / Robert Mayer -- Vespers, matins, and lauds: the life of a liberal arts college professor / Ralph James Savarese -- How white was my prairie / Mark Montgomery -- Meniscus / Robert Gray -- Once was lost / John Bryant -- Shared attention: hearing Cameron's voice / Mark Osteen -- Accidental academic, deliberate dad / Kevin G. Barnhurst -- Late fatherhood among the baptists / Andrew Hazucha -- Being a dad, studying fathers: personal reflections / William Marsiglio -- Single dad in academia: fatherhood and the redemption of scholarship / Eric H. du Plessis -- Superheroes / Stanford W. Carpenter -- Maybe it is just math: fatherhood and disease in academia / Jason Thompson -- Dreaming of direction: reconciling fatherhood and ambition / Mike Augsperger -- Making a home for family and scholarship / Ting Man Tsao -- Change is here, but we need to talk about it: reflections on black fatherhood in the academy / Jeffrey B. Leak -- Vocabularies and their subversion: a reminiscence / John Domini -- Balancing diapers and a doctorate: the adventures of a single dad in grad school / Charles Bane -- It's a chapter-book, huh: teaching, writing, and early fatherhood / Alex Vernon -- Pitcher this: an academic dad's award-winning attempt to be in two places at once / Colin Irvine -- Odd quirks / Christopher Gabbard -- The precarious private life of professor father fiction chef and other possible poignancies / Gary McCullough.
Includes bibliographical references.
Electronic reproduction.
Keywords: Fatherhood; Father and child; Electronic books